An Analysis of Injury Patterns for Drivers Based on Police Reported Frontal Crashes in Malaysia - M. N., Noordin; H., Osman; H. A., Aziz; N., Rosli; M., Widia; E. H., Sukadarin; N. S., Fauzan; H. R., Zadry; A.A., Ab Rashid (Society of Automotive Engineers Malaysia, 2021)
Most Southeast Asian countries including Malaysia have a relatively high number of traffic fatalities involving occupants of 4-wheel vehicles. The frontal impact collisions have been identified as the cause of most passenger vehicle occupant deaths. Therefore, a better understanding of real-world frontal crashes is needed in support of decision-making processes for future frontal crash test programs. One of the important elements to examine is the occupant injury patterns based on real-world crashes. Furthermore, different frontal crash configurations may result in different levels of injury severity. The objective of this study is to analyze the driver injury and body part injury levels based on police-reported frontal crashes in Malaysia. Road crash cases from 2015 to 2019 were obtained from Bukit Aman Traffic Investigation and Enforcement Department (JSPT), Royal Malaysia Police (PDRM). 81% of the cases comprised frontal crashes (full width & offset) while the rest involved sideswipe cases. Most of the drivers sustained no injury (70.77%) whereas 11.11%, 8.77%, and 6.87% suffered fatal injury, injury, and severe injury, respectively. The most frequent fatal cases among drivers involved injuries to multiple body regions for both configurations. The chi-square test revealed a significant association between the frontal crash configuration and driver injury level. The average odds ratio for fatality in frontal crashes compared to sideswipe configurations was 6.29. The rate of driver fatality per one crash has also increased marginally over the years. The study findings provide some information to support the recommendation that a full-width configuration is considered in future ASEAN NCAP frontal crash tests. Further research is also needed to fully understand real-world frontal crash impacts in Malaysia.